nifH Gene Sequencing Reveals the Effects of Successive Monoculture on the Soil Diazotrophic Microbial Community in Casuarina equisetifolia Plantations - Zhou, Liuting; Li, Jianjuan; Pokhrel, Ganga Raj; Chen, Jun; Zhao, Yanlin; Bai, Ying; Zhang, Chen; Lin, Wenxiong; Wu, Zeyan; Wu, Chengzhen (Frontiers in Plant Science, 2021)
The growth and productivity of Casuarina equisetifolia is negatively impacted by planting sickness under long-term monoculture regimes. In this study, Illumina MiSeq sequencing targeting nifH genes was used to assess variations in the rhizospheric soil diazotrophic community under long-term monoculture rotations. Principal component analysis and unweighted pair-group method with arithmetic means (UPGMA) clustering demonstrated distinct differences in diazotrophic community structure between uncultivated soil (CK), the first rotation plantation (FCP), the second rotation plantation (SCP), and the third rotation plantation (TCP). Taxonomic analysis showed that the phyla Proteobacteria increased while Verrucomicrobia decreased under the consecutive monoculture (SCP and TCP). The relative abundance of Paraburkholderia, Rhodopseudomonas, Bradyrhizobium, Geobacter, Pseudodesulfovibrio, and Frankia increased significantly while Burkholderia, Rubrivivax, and Chlorobaculum declined significantly at the genus level under consecutive monoculture (SCP and TCP). Redundancy analysis (RDA) showed that Burkholderia, Rubrivivax, and Chlorobaculum were positively correlated with total nitrogen and available nitrogen. In conclusion, continuous C. equisetifolia monoculture could change the structure of diazotrophic microbes in the rhizosphere, resulting in the imbalance of the diazotrophic bacteria population, which might be a crucial factor related to replanting disease in this cultivated tree species.